Effects of 7-step Problems Based Learning and Scientific Reasoning on Problem Solving Abilities - Amin Mustajab; Muhardjito Muhardjito; Sunaryono Sunaryono (Jurnal Pembelajaran Fisika, 2020)
The end of this study to decide how the differences in problem-solving abilities of students who take part in learning using 7-step PBL and conventional methods are reviewed from high and low scientific reasoning ability. The sample in this study (N) numbered 125 students who were selected using convenience sampling statistical techniques. The method used in this study is a quantitative research method with a factorial 2 x 2 research design. Data on problem-solving ability was analyzed using a two-way ANOVA statistical test. The results of the study show that the learning method provides statistical differences in students' problem-solving abilities. This is due to several reasons, the first PBL 7-step learning in terms of clarification of terms and concepts provides an opportunity for the teacher to intervene if students provide incorrect explanations of the problem given. Second, students are given the opportunity to establish agreed problems not only to mention them but to discuss the problem formulation and also to examine broader relevance. Third, the ability to apply the knowledge gained during learning to new situations/problems in the PBL 7-step class is better than the conventional class. Keywords: problem-solving abilities, 7-step PBL, scientific reasoning ability.DOI: http://dx.doi.org/10.23960/jpf.v8.n1.202006